Paradoxes of Sahrawi refugees' educational migration: promoting self-sufficiency or renewing dependency? - Fiddian-Qasmiyeh, E (2011)
Education is often prioritised by refugee children and families, as well as by their political representatives and international actors alike. This article explores the specificities of the Sahrawi refugee education system, focusing in particular on the nature, motivations and implications of Sahrawi refugee youths' educational migration to Cuba through a scholarship programme designed to promote self-sufficiency and socio-economic development in the Sahrawi refugee camps. Drawing upon interviews conducted with Cuban-educated Sahrawi refugees in Cuba and in their Algerian-based refugee camps I argue that, despite educational migration having become a central part of Sahrawi refugee children's, youths' and adults' imaginary landscapes, Sahrawi youths' educational migration to Cuba is ultimately paradoxical in nature, reshaping and reinforcing, rather than reducing, Sahrawi refugees' dependence upon Western aid providers. © 2011 Copyright Taylor and Francis Group, LLC.